Model-minority imperialism - Bascara, Victor, 1970- (University of Minnesota Press, 2006)
Focusing on the terms of Asian American assimilation and the rise of the model-minority myth, Victor Bascara examines the resurgence of empire as a tool for understanding the legacy of American imperialism. Model-Minority Imperialism links geopolitical dramas of twentieth-century empire building with domestic controversies of U.S. racial order by examining the cultural politics of Asian Americans in fiction, film, and theatrical productions.